System-forming criteria of modern social economy - Spanova , B.K. (BUKETOV BUSINESS REVIEW, 2019)
In the article the categorial and conceptual apparatus of the social state from the point of view of the possibilities of their influence on socio-economic development are studied. The development of institutional partnership between the public, private and non-profit sectors has been identified as one of the most important areas in the system of measures to improve the management of public sector resources. The use of the accumulated potential of these sectors and their involvement in a wide range of public services has led to a reduction in public spending on many areas of social services in the country, as well as improving their quality. In the study, systematically analyzed in the socio-economic development, based on the results of testing the author’s hypothesis, the system-forming criteria of the modern socio-economy, including the agricultural sector, are defined and systematized. In modern studies, it is said that the needs of the poor population of society in the public interest significantly reduced the ability to display. In the question of the ratio of justice and rationality, it is proved that in modern science there are several different approaches. It was concluded that the modern social state is socially responsible for the welfare of its citizens on the basis of social justice in society.